Bioinspired hyaluronic acid based nanofibers immobilized with 3, 4-difluorobenzylidene curcumin for treating bacterial infections - Patel, Pratikshkumar R.; Singam, Amarnath; Iyer, Arun K.; Gundloori, Rathna Venkata Naga (Journal of Drug Delivery Science and Technology, 2022)
Curcumin (Cur) is a natural polyphenol with multifaceted pharmacological functions, exploited extensively for biomedical applications. Traditionally curcumin is being used as an antimicrobial agent. However, to improvise the pharmacological properties, it is being modified synthetically. One of such modified Cur is 3, 4- difluorobenzylidene curcumin (CDF) which is aimed for enhancing the anti-cancer properties. Though there are reports on the studies of anti-cancer properties involving CDF, the anti-bacterial property is yet to be demonstrated. Accordingly, in our studies, we prepared bioinspired hyaluronic acid blends immobilized with CDF and fabricated non-woven nanofiber mats. These nanofiber mats were characterized and demonstrated in vitro cell culture studies, which involved cell viability, hemolysis, anti-bacterial and cell scratch assay to understand their efficacy in treating bacteria. The molecular docking studies of CDF and Cur were performed on the dihydrofolate reductase (DHFR) enzyme receptor, which is an essential protein of S.auerus (Staphylococcus aureus). The results of MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) assay, and hemolysis of the respective nanofiber mats with Cur and CDF showed non-toxicity and were compatible with blood cells. Further, the cell proliferation and adherence recorded >60% fibroblast cells for the nanofiber mats. The anti-bacterial property of Cur and CDF was similar. The in vitro release studies for the respective Cur and CDF loaded nanofiber mats recorded a release of 25 and 37%, respectively. From these studies, we concluded that the CDF sustained its antibacterial property in addition to the improved anti-cancer property; hence CDF being synergetic, it will have a better scope in cancer therapy.
Keywords: anti-bacterial; curcumin; nanofibers; tissue engineering; wound Healing